Gender Gap in Earnings in Vietnam : Why Do Vietnamese Women Work in Lower Paid Occupations? - Chowdhury, Iffat; Johnson, Hillary C.; Mannava, Aneesh; Perova, Elizaveta (World Bank, Washington, DC, 2018)
Differences in earnings between male and female workers persist in developed and developing countries despite a narrowing of gender gaps in educational attainment over the past half-century. This paper examines the gender wage gap in Vietnam and shows that a nontrivial part of the gap is associated with occupational sorting. The paper considers three explanations for why occupational sorting emerges. First, it explores whether women sort into occupations with better nonmonetary characteristics, such as paid leave and shorter hours. The data from Labor Force Surveys support this hypothesis. Second, it checks if occupational sorting among the adult labor force is driven by social norms about gender roles learned and internalized at an early age. To do so, the paper checks for evidence of sorting in the aspirations of 12-year-old children. Specifically, the analysis simulates what the gender wage gap would be if boys and girls pursued the occupations they aspired to at age 12, and the distribution of salaries remained unchanged. The paper does not find support for the hypothesis that gender norms drive occupational sorting by inducing aspirational sorting at an early age. Finally, for individuals with higher education, the paper checks if occupational sorting occurs during the school-to-work transition, when women face higher barriers in finding a job in their field of study. The analysis does not find evidence to support this last hypothesis. Overall, the findings suggest that in Vietnam gender-specific preferences for nonmonetary job characteristics play a key role in the emergence of occupational sorting.